PECVD and Thermal Gate Oxides on 3C vs. 4H SiC: Impact on Leakage, Traps and Energy Offsets. (1st January 2015) - Gutt, T.; Przewlocki, H. M.; Piskorski, K.; Mikhaylov, A.; Bakowski, M.
Abstract : Energy-band model offsets, trap density distributions and gate leakage characteristics of MOS capacitors with PECVD and thermal gate oxides on 3C-SiC and 4H-SiC were compared. The difference in trap energy distributions between the polytypes confirmed the lesser 3C-SiC polytype vulnerability to near-interface traps (NIT), which are alternatively found in high density in the 4H-SiC. It was also shown that the quality of the PECVD oxides obtained in this experiment were comparable to that of the thermal oxide. Only a slight increase of leakage current was observed in the PECVD oxides due to oxide inhomogeneity in the lower electric field interval of the Fowler-Nordheim range. Finally, the energy band model of the SiC MOS devices was described quantitatively for different combinations of polytype and oxidation method, which illustrated the influence of technological processing on the energy offsets and potentials, and could be used for further development of the devices and processes.